2020
DOI: 10.1371/journal.pbio.3000987
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin treatment impacts resistance in off-target populations of vancomycin-resistant Enterococcus faecium

Abstract: The antimicrobial resistance crisis has persisted despite broad attempts at intervention. It has been proposed that an important driver of resistance is selection imposed on bacterial populations that are not the intended target of antimicrobial therapy. But to date, there has been limited quantitative measure of the mean and variance of resistance following antibiotic exposure. Here we focus on the important nosocomial pathogen Enterococcus faecium in a hospital system where resistance to daptomycin is evolvi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…Treatment then imposes selection, which can enrich for these resistant clones. This process of resistance emergence has been observed in hospital patients— E. faecium isolated from patient perirectal swabs are more resistant following daptomycin treatment, and genomic data suggests that this resistance arises de novo within patients [4]. Here, we observe the same process in a mouse model.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Treatment then imposes selection, which can enrich for these resistant clones. This process of resistance emergence has been observed in hospital patients— E. faecium isolated from patient perirectal swabs are more resistant following daptomycin treatment, and genomic data suggests that this resistance arises de novo within patients [4]. Here, we observe the same process in a mouse model.…”
Section: Discussionsupporting
confidence: 76%
“…These treatments rely on antibiotic antagonists, which bind to or inactivate antibiotics locally in the intestines. Daptomycin is an especially attractive antibiotic target, because daptomycin resistance emerges easily and often in the gut through point mutations, as shown here in our mouse model and in patient data [4]. Additionally, cholestyramine is an attractive drug to repurpose as an adjuvant, because it is an FDA-approved drug that has been in use with minimal side effects for over 50 years [30,31], and it could inexpensively be repurposed to prevent the spread of resistance.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This led to a first observation: a variant of the persistent clone with decreased daptomycin susceptibility spread among 17 patients during the outbreak of 2018. In the first place, this variant was likely selected within host, either during treatment of one of the sampled individuals or in the off-target carriage population of any unsampled individual, as suggested by Kinnear et al ( 51 ). However, while within-host evolution of variants with decreased daptomycin susceptibility is commonly reported, their clonal spread is rarely observed ( 52 54 ).…”
Section: Discussionmentioning
confidence: 98%
“…Pre–liver transplant colonization with VRE has been associated with higher rates of post–liver transplant VRE infection as well as increased length of stay, morbidity, and mortality when compared with noncolonized recipients [ 6 , 7 , 43 , 44 ]. Recent data have shown that daptomycin resistance can develop in screening fecal cultures and that the development of daptomycin resistance is 50% higher in those exposed to daptomycin [ 45 , 46 ]. However, to date, there are limited data focusing on infection prevention strategies in DRE-colonized and -infected liver transplant patients.…”
Section: Discussionmentioning
confidence: 99%